A 'fit' microbiota to potentiate cancer immunotherapy. Issue 1 (December 2015) - Rescigno, Maria
Abstract Cancer immunotherapy is very effective and leads to a long-term response in certain patients. Yet, the variability observed in this response indicates that additional factors related to the host must influence the activity of the treatments. Recent research suggests that the microbiota might play an important part in this variability.